2008
DOI: 10.2193/2008-004
|View full text |Cite
|
Sign up to set email alerts
|

Elk Calf Survival and Mortality Following Wolf Restoration to Yellowstone National Park

Abstract: We conducted a 3-year study (May 2003-Apr 2006 of mortality of northern Yellowstone elk (Cervus elaphus) calves to determine the cause for the recruitment decline (i.e., 33 calves to 13 calves/100 adult F) following the restoration of wolves (Canis lupus). We captured, fit with radiotransmitters, and evaluated blood characteristics and disease antibody seroprevalence in 151 calves 6 days old (68M:83F). Concentrations (x, SE) of potential condition indicators were as follows: thyroxine (T4; 13.8 lg/dL, 0.43), s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
301
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(327 citation statements)
references
References 105 publications
(232 reference statements)
20
301
3
Order By: Relevance
“…v www.esajournals.org calves (Barber-Meyer et al 2008). However, bear predatory efficiency is limited in time, only until the calves are 4 weeks old (Rauset et al 2012), and bears mainly access larger moose by scavenging other predators' kills (Swenson et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…v www.esajournals.org calves (Barber-Meyer et al 2008). However, bear predatory efficiency is limited in time, only until the calves are 4 weeks old (Rauset et al 2012), and bears mainly access larger moose by scavenging other predators' kills (Swenson et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In North America, both black (U. americanus) and brown (U. arctos) bears commonly prey on neonatal cervids, taking a large percentage of the annual offspring that are less than 1 month old, and these effects could be additive. In Yellowstone National Park, bears killed more elk (Cervus elaphus) calves than did gray wolves, coyotes (Canis latrans), and pumas combined (43). In Europe, roe deer densities were significantly lower in areas with sympatric wolves and lynx than in areas with wolves alone or areas where both predators were absent (24,34).…”
Section: Other Large Carnivoresmentioning
confidence: 98%
“…Because of differences in their ecology and human tolerance, pumas are able to persist in areas with much higher levels of human land use than are gray wolves, even though these two carnivores are of similar size. Such differential predator species loss in the face of landscape changes may be especially critical if synergism among multiple large carnivores within predator guilds is required to maintain control over prey populations (34,43). These and other carnivore species make kills in different habitats, or scavenge to supplement their diets, which can determine the nature and rates of prey kills and consumption (53, 69).…”
Section: Reviewmentioning
confidence: 99%
“…These figures suggest that the impact of bear predation on the ungulate population is probably very small. However, in order to be sure, ungulate mortality would have to be studied, requiring fawns to be tagged (Barber-Meyer et al 2008;Swenson et al 2007). …”
Section: Discussionmentioning
confidence: 99%
“…Bears may also kill adult ungulates, but mainly concentrate on calves in the first 4 weeks after birth in spring and early summer (Barber-Meyer et al 2008;Zager and Beecham 2006). In a review of black (Ursus americanus) and brown bear predation on ungulates in North America, Zager and Beecham (2006) suggested that predation is additive at low ungulate densities and can become compensatory as prey density approaches carrying capacity.…”
Section: Introductionmentioning
confidence: 99%